Pharmacokinetic Profile of Astaxanthin Nanoemulsion Using HPLC (High-Performance Liquid Chromatography) With Oral Routes - Nurdianti, Lusi; Setiawan, Fajar; Rusdiana, Taofik; Sofyan, Iyan; Lisnawati, Elis; Firmansya, Ardianes (Universitas Padjadjaran (Unpad), 2023)
Astaxanthin is a very strong antioxidant of the xanthophyll carotenoid group with very lipophilic properties, so in oral administration, its bioavailability is very low. This study aimed to examine the differences in the pharmacokinetic profile of astaxanthin and astaxanthin nanoemulsion via the oral route using the HPLC method. Research methods include validation methods using HPLC and continued determining pharmacokinetic profiles to determine whether astaxanthin in plasma is validated. The plasma was deproteinized with ethanol: tetrahydrofuran (1: 9), mobile phase Methanol: water milliQ: ethyl acetate (82:8:10 (v/v)), the flow rate is 1.2 mL/min, wavelength 474 nm and the sample measured isocratic. Calibration curves 0.25-10 mg/L,% Recovery 102.92, 103.11 and 102.25,% RSD 1.33, 1.65 and 2. The HPLC method is fast, simple, and can be used for routine analysis of astaxanthin. The results showed that in the astaxanthin nanoemulsion, there was an increasing in Cmax and AUC0-∞ which affected increasing the bioavailability value. Therefore, it was concluded that the study showed the presence of astaxanthin in nanoemulsions has greater absorption power than pure astaxanthin. Keywords: Pharmacokinetic profile, Astaxanthin, Validation of the HPLC method, Oral route